Stretchable large-area transparent nanowire composite arrays for label-free multimodal interrogation of cardiac physiology - Nathaniel T. Quirion; Bridget R. Alber; Chenghe Dong; Amy Fehr; Qinai Zhao; Nora Shields; Ze Yang; Hangbo Zhao; Matthew W. Kay; Luyao Lu (Proceedings of the National Academy of Sciences, 2026)
Simultaneous interrogation of cardiac electrophysiological and metabolic processes is essential for investigating and treating heart disease. Key challenges remain in creating stretchable multimodal bioelectronic devices capable of organ-scale, label-free probing of electrophysiology and metabolism in vivo. Here, we present stretchable, scalable, large-area transparent microelectrode arrays (MEAs) that integrate up to 144 microelectrodes and interconnects, enabling a centimeter-scale field of view to tackle these challenges. The microelectrodes consist of conductive polymer-coated metal nanowire composites with outstanding optical transparency and electrochemical performance for both electrophysiological sensing and electrical pacing. These large-area arrays exhibit excellent yield, uniformity, biocompatibility, and mechanical deformability like native cardiac tissue. They successfully achieve in vivo spatiotemporal mapping of electrophysiological activity together with colocalized label-free autofluorescence imaging of metabolism across all four beating heart chambers under clinically relevant conditions in small animals, including ischemia, arrhythmia, and device-delivered electrotherapy. The platform offers methodological opportunities to advance basic and clinical cardiology.